Developing Competencies for Middle Level Managers Across Functional Areas - A Study in an Indian BPO - Prageetha Raju, G.; Kulkarni, Smita (Prabandhan: Indian Journal of Management, 2011)
The study deals with developing competency profiles for middle level managers at Zeal Business Support Services , an Indian BPO in India. The different competencies that were required for a job were identified using task based job analysis and interviewing the job holders and cross verifing from the reporting managers. The identified competencies were developed into competency profiles with their respective proficiency levels. There were a total of 21 job profiles that were assessed across eight different departments in the BPO. Relationships pertaining to the job, The role profile definition, and The KRAs in detail forms the first phase of the study. Then, functional and behavioral competencies are identified through a four-step methodology followed by development of a consolidated competency dictionary that contains all the explanations with respect to competencies of the position holders. Delphi technique is used to arrive at a consensus on the competencies required.